PENGARUH KEPEMIMPINAN, LINGKUNGAN KERJA, KOMPENSASI, DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN: STUDI LITERATUR - Ahmad Shobirin; Alkadri K. Siharis (Transpublika Publisher, 2022)
Employee performance is the result of a person's work in carrying out the tasks assigned to him. This study aims to determine the relationship between leadership, work environment, compensation, and work motivation as factors that affect employee performance. The method used in this research is literature study using secondary data. The secondary data sources obtained are the results of previous research with related topics and published in accredited national journals in the period 2014 to 2022. The scientific articles analyzed were 25 articles. Based on the analysis of the literature review, the results obtained that leadership, work environment, compensation, and work motivation each have a significant and positive effect on employee performance.